Enhancing Student Engagement Through Collaborative Learning (2021)
ABSTRACT: This study is an action research project carried out with seventh graders at Institucion Educativa Juan María Céspedes; a public institution located in Belén, Medellín. The aim of this project was to enhance student engagement through the implementation of collaborative learning strategies developed in pair work and group work. The data collection method included a Cooperating Teacher interview, a student survey, and observations registered in the student-teacher’s journal. Data were analyzed using the triangulation method with all the sources. The results showed that promoting interactions among students, allowing them to form the groups under their own criteria, increase their confidence for participating in class, create an enjoyable experience that facilitates their interest in learning and develop autonomy, enhancing student engagement.